Hydroxychloroquine improves pregnancy outcomes of women with positive antinuclear antibody spectrum test results - Ye, Shenglong; Liu, Yuanying; Zhao, Xueqing; Ma, Yue; Wang, Yongqing (Frontiers in Medicine, 2023)
Background Hydroxychloroquine (HCQ) has often been empirically applied to antinuclear antibody spectrum (ANAs) positive populations, and whether HCQ can also improve perinatal outcomes in this population remains controversial. The study was designed to investigate the effect of HCQ on adverse pregnancy outcomes associated with placental dysfunction in patients with a positive ANAs test result. Methods Univariate and multivariate analyses of the effect of HCQ on pregnancy outcomes in pregnant women with positive ANAs test result from 2016 to 2020 in our centre; and ANA-positive patients among them were divided into a weakly positive group and a positive group. Stratified and interactive analyses of the value of HCQ in improving pregnancy outcomes were performed for each subgroup. Results (i) A total of 261 cases were included, accounting for 30.60% of pregnancy complicated with an autoimmune abnormality, 65.12% of whom used HCQ during pregnancy. (ii) The application of HCQ significantly reduced the incidence of early-onset preeclampsia (1.18% vs. 12.09%, P=0.040) and small-for-gestational-age infants (10.06% vs. 25.84%, P=0.003) in the ANAs-positive population, increased birth weight (3075.87±603.91 g vs. 2847.53±773.73 g, P=0.025), and prolonged gestation (38.43±2.31 vs. 36.34±5.45 weeks, P<0.001). (iii) A total of 185 ANA-positive patients were stratified according to titres. The rate of HCQ usage in the positive group was significantly higher than that in the weakly positive group (81.03% vs. 58.27%, P=0.003). (iv) Stratified univariate analysis showed that HCQ usage in the ANA-positive group could reduce the incidence of preeclampsia (2.13% vs. 27.27%, P=0.019) and prolong gestation (38.29±2.54 vs. 34.48±7.68 weeks, P=0.006). In the weakly positive group, HCQ significantly reduced the incidence of preeclampsia (6.76% vs. 28.30%, P=0.002), early-onset preeclampsia (1.35% vs. 13.21%, P=0.027), small-for-gestational-age infants (7.89% vs. 35.19%, P<0.001). Multivariate regression analysis showed that HCQ significantly reduced the incidence of preeclampsia in both groups. Intergroup interaction analysis showed no significant difference in the value of HCQ in reducing the incidence of preeclampsia between the two groups. Conclusions ANAs positivity is an important type of abnormal autoimmunity in pregnancy. HCQ can be a choice for this population to improve adverse pregnancy outcomes related to placental dysfunction, such as preeclampsia.